Pengaruh Non Performing Financing, Financing to Deposit Ratio, dan Capital Adequacy Ratio terhadap Tingkat Bagi Hasil Deposito Mudharabah - Oktaviani, Nurul Rizka; Riyadi, Selamet (Jurnal Ilmu Manajemen, 2021)
This study aims to analyze the effect of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR) on the profit sharing rate of mudharabah deposits at Bank Syariah Mandiri 2010-2019. The data used in this study are data from the complete annual financial reports for 2010-2019. The analysis technique used in this research is multiple regression analysis. The results showed that partially the Non Performing Financing (NPF) and the Financing to Deposit Ratio (FDR) had no effect on the profit sharing rate of mudharabah deposits. Meanwhile, the Capital Adequacy Ratio (CAR) partially has a significant negative effect on the profit sharing rate of mudharabah deposits. Simultaneously, Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR) have a significant effect on the profit sharing rate of mudharabah deposits. The results of this study can be used as an assessment material in maintaining and improving the bank's financial performance in order to be better and further researchers can expand the limitations contained in this study, namely by expanding the object of research in order to obtain better research results.